2018
DOI: 10.1016/j.envpol.2018.04.112
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the deposition environment and long-term fate of Chernobyl 137Cs at the floodplain scale through mobile gamma spectrometry

Abstract: Cs-137 is considered to be the most significant anthropogenic contributor to human dose and presents a particularly difficult remediation challenge after a dispersal following nuclear incident. The Chernobyl Nuclear Power Plant meltdown in April 1986 represents the largest nuclear accident in history and released over 80 PBq of Cs into the environment. As a result, much of the land in close proximity to Chernobyl, which includes the Polessie State Radioecology Reserve in Belarus, remains highly contaminated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Real-time maps with color-scaled ambient dose rates and gamma-ray energy spectra can be output. The detected energy peaks of radiocesium ( 134 Cs and 137 Cs) registered in the nuclear library (i.e., detected net count values) and their associated confidence intervals were obtained for the region of interest (with levels 1-10 used as reference values) 7,39 .…”
Section: Survey Of Ambient Rates and Radionuclidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time maps with color-scaled ambient dose rates and gamma-ray energy spectra can be output. The detected energy peaks of radiocesium ( 134 Cs and 137 Cs) registered in the nuclear library (i.e., detected net count values) and their associated confidence intervals were obtained for the region of interest (with levels 1-10 used as reference values) 7,39 .…”
Section: Survey Of Ambient Rates and Radionuclidesmentioning
confidence: 99%
“…Long-term environmental monitoring as well as further decontamination efforts should continue around the FDNPS, including Tomioka Town. On the other hand, the external exposure level and the decontamination effects on landscape within the difficult-to-return zone have not been evaluated concretely, although data from the literature, databases and websites have been reported by the national and local governments [4][5][6][7][8][9]12,13 . Especially, recent reports on the decontamination effect on landscape are not sufficiently published 14 .…”
mentioning
confidence: 99%
“…Small scale variation in contamination distribution is particularly important, as more recent studies have demonstrated that orders of magnitude of change can be observed in areas closer to the Chernobyl nuclear power plant (Golosov, 2003;Golosov et al, 2000;Adam Varley et al, 2017;Vitaly et al, 2019Vitaly et al, , 2018. In part this variation is due to remobilisation, but mainly it is down to finer scale deposition patterns dictated by localised meteorological events in 1986 (Varley et al, 2018). Therefore, basing wood activities for an entire forest stand from TR derived from limited soil samples leaves a study particularly vulnerable to very large uncertainties on final estimates.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional methods of depth estimation such as core sampling and logging are slow and have limited spatial sampling extent because of their intrusive nature. Furthermore, the nonintrusive methods reported in [5,[7][8][9][10][11][12][13][14] are either based on regressional models whose parameters typically have no physical significance or are limited to specific radioactive sources. Also, other nonintrusive methods reported in [15,16] use specialised shielding and collimator arrangements while those that employ machine learning [17][18][19] require significant amount of data to train the algorithms.…”
Section: Introductionmentioning
confidence: 99%